STRATEGI PEMBELAJARAN PENGETAHUAN DASAR KOMPUTER BAGI MAHASISWA JURUSAN KTP FIP UNP - Meldi Ade Kurnia Yusri, S.T., M.Pd.T. (Pedagogi: Jurnal Ilmu Pendidikan, 2017)
The term "computer" in the modern era as it is today is not a new thing anymore. If people ask someone who has a background that is not the field of Information and Communication Technology (ICT), of course the answer will be general and not deep. However, if the person questioned about the term "computer" has an ICT background, of course the answer given will be more in depth and understand what are the supporting components of the computer. Just as if someone asked the students of the Department of Education and Curriculum of FIP UNP about the term "computer", the student should be able to expain in more depth. This study uses a qualitative approach, in which the authors try to express and understand the reality that exist in the field of learning strategy of basic computer knowledge for students of Curriculum and Education Technology FIP UNP. Based on the results of the observations that the authors obtain in the field, in terms of preparation, lecturers have prepared lecture contracts, learning tools in the form of syllabus, SAP and teaching materials, preparation of facilities and learning infrastructure. In the process of learning strategy of basic computer knowledge for students of Curriculum and Technology Education Department of FIP UNP, the lecturer gives an assessment with the principle of justice and objectivity.